Association between maternal intimate partner violence and health-related quality of life in their preschool children: The mediating role of maternal parenting styles - Luo, Shengyu; Lin, Li; Chen, Weiqing; Li, Chunrong; Ren, Yan; Zhang, Meng; Guo, Vivian Yawei (Frontiers in Psychiatry, 2022)
Background: Although intimate partner violence (IPV) against women is a public health issue around the world, there is a lack of evidence regarding the impact of maternal IPV on preschool children’s health-related quality of life (HRQOL). Therefore, the aim of this study was to investigate the association between maternal IPV and HRQOL among Chinese preschool children, as well as the mediating role of maternal parenting styles. Methods: A cross-sectional study was conducted with 4243 mother-child dyads who attended preschools. Mothers self-reported their parenting styles and experience of IPV. Children’s HRQOL was collected through mother-proxy report with the Pediatric Quality of Life Inventory version 4.0 (PedsQL 4.0). Multivariate linear regression analysis was conducted to evaluate the association between maternal IPV and children’s HRQOL. Mediation models were further applied to explore the possible mediating role of maternal parenting styles. Results: Of the included mothers, 7.4% had experience of IPV. Compared to children of mothers without any IPV exposure, those of mothers with experience of IPV had significantly lower scores in all HRQOL dimensions and summary scales. After adjustment for covariates, maternal IPV was significantly associated with children’s lower physical health summary score, psychosocial health summary score, and total scale score. Mediation analysis showed that negative parenting styles, i.e., rejection and overprotection, mediated such associations, but not for the emotional warmth. Conclusions: Our findings indicated the need to screen maternal IPV supplemented with targeted interventions focusing on parenting styles, in order to mitigate the negative impact of maternal IPV on children’s HRQOL.